Association of the Commitments and Responsibilities of the Caregiver Within the Family to the Disease Activity in Patients With Rheumatoid Arthritis: A Report From Turkey - Emel SABAZ KARAKECİ and Derya ÇETİNTAŞ and Arzu KAYA (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the commitments and responsibilities of the family caregiver of rheumatoid arthritis patients and determine the association of these to the disease activity. Patients and methods: The study included a total of 240 subjects, consisting of 60 rheumatoid arthritis patients (8 males, 52 females; mean age 50.4±11.1 years; range 25 to 76 years) with their respective 60 primary caregivers (42 males, 18 females; mean age 43.1±15.3 years; range 12 to 77 years) and 60 OA patients (7 males, 53 females; mean age 62.8±9.0 years; range 45 to 85 years) with their respective 60 primary caregivers (38 males, 22 females; mean age 47.6±13.2 years; range 27 to 87 years). Disease severity and pain of patients were assessed through visual analog scale. Sedimentation and C-reactive protein values were recorded during routine visits. Patients were stratified by disease activity that was determined by disease activity score-28. Caregivers of patients evaluated disease severity and pain by visual analog scale, and completed Caregiver Reaction Assessment (CRA) and Caregiver Strain Index questionnaires. For a more objective assessment, tasks related to care, household, and assistance and allocated time periods for each group of tasks were queried. Results: When CRA and Caregiver Strain Index were compared in terms of disease activity, patients significantly differed in impact on schedule subscale of CRA (p<0.05). Similarly, disease activity was significantly associated with impact on finance subscale of CRA (p<0.05). Impact on health subscale of CRA was also correlated with disease activity; i.e., the higher the disease activity score-28, the more negative impact on health of the caregiver. Conclusion: Patient care is an important part of rheumatoid arthritis management. Chronic diseases form commitment on patient’s caregiver. That the care of the patient may be associated with many factors related to both the patient and the caregiver should not be underestimated. We suggest that caregiver’s strain may be correlated with disease activity.